2018
DOI: 10.15406/joentr.2018.10.00372
|View full text |Cite
|
Sign up to set email alerts
|

Middle ear osteoma: case report and review of literature

Abstract: Osteomas are benign lesions that arise in the temporal bone commonly in the external canal. However middle ear osteomas are extremely rare. They are usually asymptomatic and discovered incidentally or may present with conductive hearing loss. This article reports a case of middle ear promontory osteoma with review of literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…We found that only 9 other cases have been reported since Yoon et al. published their findings in 2014 ( Toro et al., 2014 ; Abouzayd and Seghir, 2015 ; Hamid et al., 2018 ; Curtis et al., 2014 ; Gülşen, 2019 ; Molher et al., 2018 ), and reported the 46th case of MEO ( Table 1 ). Unfortunately, we were unable to obtain the full text of one paper in which 2 cases of MEO were reported.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…We found that only 9 other cases have been reported since Yoon et al. published their findings in 2014 ( Toro et al., 2014 ; Abouzayd and Seghir, 2015 ; Hamid et al., 2018 ; Curtis et al., 2014 ; Gülşen, 2019 ; Molher et al., 2018 ), and reported the 46th case of MEO ( Table 1 ). Unfortunately, we were unable to obtain the full text of one paper in which 2 cases of MEO were reported.…”
Section: Discussionmentioning
confidence: 62%
“…In the present review, of the 44 cases, 40 patients underwent surgical treatment, and only 4 patients were managed conservatively ( Table 1 , Table 2 ). ( Yoon et al., 2014 ; Hamid et al., 2018 ; Gülşen, 2019 ; Molher et al., 2018 ; Barbosa et al., 2007 ). Depending on the localization and size of the mass as well as the surgeon’s preference, microscopic retroauricular or endaural and endoscopic transcanal approaches can be used to remove the MEO.…”
Section: Discussionmentioning
confidence: 99%
“…10 Sometimes the peripheral rim of reactive bone sclerosis is so extensive that the underlying radiolucent nidus may result obscured. 11 Computed Tomography is the imaging technique of choice for osteoma, being advantageous for detection and characterization of both the nidus and the peripheral sclerosis. 3 It is particularly helpful for small osteomas, for those lesions which show less peripheral bone sclerosis (especially medullary and subperiosteal types), and in all those cases where standard radiographs are not clearly conclusive.…”
Section: Diagnosismentioning
confidence: 99%